2013
DOI: 10.1037/a0034652
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of parenting stress trajectories in premature infant–mother dyads.

Abstract: This prospective longitudinal study examined predictors of parenting stress trajectories over time in a sample of 125 mothers and their preterm infants. Infant (multiple birth, gestational age, days hospitalized, and neonatal health risks) and maternal (socioeconomic, education, depressive symptoms, social support, and quality of interaction during infant feeding) characteristics were collected just prior to infant hospital discharge. Parenting stress and maternal interaction quality during play were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 51 publications
2
49
2
3
Order By: Relevance
“…Communication stress was peculiarly present in parents who had experienced multiple births. As similar effects are already reported elsewhere [58,59], we assume that multiple birth and having more than one child in the NICU affects the risk of communication stress, requiring additional communication needs. Thus, additional support resources for parents of multiples may be of particular benefit.…”
Section: Discussionmentioning
confidence: 62%
“…Communication stress was peculiarly present in parents who had experienced multiple births. As similar effects are already reported elsewhere [58,59], we assume that multiple birth and having more than one child in the NICU affects the risk of communication stress, requiring additional communication needs. Thus, additional support resources for parents of multiples may be of particular benefit.…”
Section: Discussionmentioning
confidence: 62%
“…In a study with just two time periods, it was also reported that the Child Domain on the PSI was significantly higher for the mothers of very preterm compared with full-term children, with a trend towards change over time 14. In contrast, both Kaaresen et al 21 and Spinelli et al 9 reported no significant change in parenting stress for mothers of preterm infants over time. In the current study, in addition to Total Stress Scores, the Difficult Child subscale on the PSI-SF (the questions being very similar to those on the Child Domain on the PSI) indicated a significant change over time between the preterm and term mothers.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, it was found that the stress levels did not change as the child grew older. Spinelli et al 9 examined parenting stress at three time points—4, 24 and 36 months in a study of preterm infants born in 2002–2005. The results indicated that there was only a slight increase in stress over time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies have suggested mothers of multiple birth infants have more distress and less positive interactions than mothers of singletons (Holditch-Davis et al, 2007; Spinelli, Poehlmann, & Bolt, 2013). Thus, determining if the interventions had differential effects on mothers of multiples and mothers of singletons would be interesting.…”
Section: Discussionmentioning
confidence: 99%